2017
DOI: 10.1136/bmjopen-2017-016149
|View full text |Cite
|
Sign up to set email alerts
|

Trends in readmission rates for safety net hospitals and non-safety net hospitals in the era of the US Hospital Readmission Reduction Program: a retrospective time series analysis using Medicare administrative claims data from 2008 to 2015

Abstract: ObjectiveTo compare trends in readmission rates among safety net and non-safety net hospitals under the US Hospital Readmission Reduction Program (HRRP).DesignA retrospective time series analysis using Medicare administrative claims data from January 2008 to June 2015.SettingWe examined 3254 US hospitals eligible for penalties under the HRRP, categorised as safety net or non-safety net hospitals based on the hospital’s proportion of patients with low socioeconomic status.ParticipantsAdmissions for Medicare fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 19 publications
1
30
0
Order By: Relevance
“…While previous studies examined trends in emergency readmission rates for different types of hospitals 45 and surgical emergency readmission rates for selected patient subgroups as a measure for quality of care in the USA, 46 this is the first study that provides a comprehensive overview of trends in risk-adjusted, 30-day emergency readmissions and variation in England over a 10-year period and disaggregated for nine clinical conditions. One study that had reported on trends of English emergency readmission rates before focused on a period up to May 2010, but did not disaggregate by clinical condition.…”
Section: Discussionmentioning
confidence: 99%
“…While previous studies examined trends in emergency readmission rates for different types of hospitals 45 and surgical emergency readmission rates for selected patient subgroups as a measure for quality of care in the USA, 46 this is the first study that provides a comprehensive overview of trends in risk-adjusted, 30-day emergency readmissions and variation in England over a 10-year period and disaggregated for nine clinical conditions. One study that had reported on trends of English emergency readmission rates before focused on a period up to May 2010, but did not disaggregate by clinical condition.…”
Section: Discussionmentioning
confidence: 99%
“…37,38 In an analysis of CMS hospital-level data on COPD, as readmissions fell, all-cause risk-standardized mortality increased, 39 though COPD-specific mortality has not been evaluated. The potential disproportionate penalization of safety net hospitals is another concern, [40][41][42][43] particularly in COPD. 44 The effects of the HRRP expansion to include COPD on these outcomes require further study.…”
Section: Discussionmentioning
confidence: 99%
“…Our findings are similar to other recent papers by Figueroa and colleagues who found similar reductions in disparities using national data. 21 In addition, previous studies have shown that safety-net hospitals have seen greater improvements in readmissions, 3,22 but the fact that disparities also decreased suggests that these constrained hospitals were still able to reduce readmissions for Black patients. Nonetheless, safetynet hospitals are among the most adversely affected by HRRP.…”
Section: Discussionmentioning
confidence: 99%